Synthesis of Dimethyl (Z)-((3-oxoindolin-2-ylidene) (aryl)methyl)phosphonates Through Tandem Cadogan and Arbuzov Reactions - Nicolai A. Aksenov; Dmitrii A. Aksenov; Daniil D. Ganusenko; Alexander E. Kurlikov; Alexander P. Barbolin; Polina S. Karaseva; Alexander V. Aksenov (Molbank, 2025)
A novel method employing a tandem Cadogan and Arbuzov reaction sequence has been developed, providing access to a series of previously unreported dimethyl (Z)-((3-oxoindolin-2-ylidene)(aryl)methyl)phosphonates. Restricted rotation of the aryl substituent, particularly in the presence of ortho substituents, gives axial chirality to these compounds.